Geochronology of the granitic rocks of the Real Cordillera of Bolivia - Ibanez, Alvaro Rodrigo Iriarte (2021)
The present PhD thesis corresponds to a geochronological study of granitoids and their country rocks located at the Cordillera Real of Bolivia. Three scientific papers are presented. The first paper is about the geologic history of the Huayna Potosí and Zongo plutons as well as their country rocks, using Rb/Sr, K/Ar and U/Pb isotopic systems. Rb/Sr analyses of metapelitic country rocks of early Paleozoic (Amutara and Cancañiri Formations) yielded a Rb-Sr isochron age of 344 ± 38 Ma, indicating the action of an early Gondwanide regional event. A five-point Rb-Sr isochron from the Huayna Potosi pluton yielded an age of 224 ± 28 Ma. For the Zongo pluton, many of the zircon grains obtained from one sample of its Kuticucho facies yielded extremely high uranium content, which produced reverse discordant apparent ages. However, due to the fair alignment of the analytical points, it was made a regression calculation and the interception of the Concordia curve resulted in an imprecise age of 220 ± 20 Ma. The final magmatic crystallization and the intrusion of plutons in the central part of the Cordillera Real have occurred close to 221.5 ± 2.0 Ma. The reverse discordant apparent ages can be related to fluid enrichments at the final crystallization stage of these plutons. For the second paper, a geochronological study of U/Pb zircon ages of the other plutons of the Cordillera Real is presented. It is based on SHRIMP data. Their tectonic setting, chemical and ore compositions make them part of the so-called Inner Magmatic Arc, which differs from the current Magmatic Arc located to the west. The Triassic group yielded the following results: 239 ± 2 Ma for the Huato granite, 231 ± 1 Ma for the Illampu granodiorite, 221 ± 3 Ma for the Huayna Potosí granite and 223 ± 2 Ma for the Taquesi granodiorite. Magmatic pulses can be calculated at 223, 230, 242 and 248 Ma. For the Oligocene group ages of 27 for two samples of the Quimsa Cruz batholith were obtained. Relatively abundant zircon inheritance was found in these cold granitoids, with ages suggesting provenance from early Paleozoic metapelites. This relatively abundant xenocrystic inheritance probably records the influence of the subduction process acting during the Gondwanide orogeny (336-205 Ma) as an overall subduction arc environment, punctuated at its final stage with the imprint of a continental rifting (245-220 Ma). Finally, the third paper deals with the relationship of the plutons of the Cordillera Real and their country rocks. It uses U/Pb zircon ages. SHRIMP ages are from xenocrystal zircons of the plutons and LA-ICP-MS ages are from detrital zircons of metasedimentary units. High statistical correlation suggests assimilation of metasedimentary units by felsic melts. Ages distribution ranges from 300 to 2300 Ma. High peaks of Cambrian to late Neoproterozoic ages (500-750 Ma) are observed. There are discussed several possibilities about the provenance of these detrital zircons: Brasiliano or Puncoviscano belts, an in situ hidden belt within the Central Andes or recycling of pre-existent sedimentary rocks bearing those detrital zircons.